Penguatan Branding dan Pemasaran Digital Usaha Rumahan bagi Ibu-Ibu PKK Kabupaten Karawang - Pristiana Widyastuti; Kurnianing Isololipu; Antonius Widi Hardianto (Universitas 17 Agustus 1945 Jakarta, 2026)
This program aims to enhance the capacity of PKK women (members of the Family Welfare Empowerment Organization in Indonesia), as home-based MSME entrepreneurs in utilizing digital marketing and strengthening business branding. The program was conducted with 32 PKK women participants through training and mentoring methods. The training materials included the use of social media for digital marketing, writing promotional messages based on the AIDA (Attention, Interest, Desire, Action) model, product photography techniques, and the creation of digital promotional designs using the Canva application. The results of the program showed an improvement in participants’ abilities to utilize social media for business promotion, create promotional captions, produce more attractive product photos, and independently design digital promotional content. The evaluation also indicated that the training materials were relevant to the participants’ needs and could be directly applied in their daily business activities. This program is expected to help home-based MSME entrepreneurs expand their market reach and improve the competitiveness of their digital-based businesses